The Role of Technological Innovation in International Economic Integration in Park Chung-hee’s South Korea and Deng Xiaoping’s People’s Republic of China - Figueroa Gómez, Camila; Navarro Oyarzún, Camilo (Latin American Journal of Asian Studies, 2025)
This article analyzes the role of technological innovation in the perspective of Park Chung-hee and Deng Xiaoping regarding the international economic integration of South Korea and the People’s Republic of China, respectively. Despite their ideological and political differences, both leaders adopted a similar political economy approach to drive development and position their coun- tries within the international order. Facing unique geopolitical and economic contexts, both South Korea and China opened their economies to international trade and foreign investment while promoting research and technological development as a respon- se to their internal and external challenges. Using a diachronic comparative approach, this study examines how both leaders conceived technology as a strategic element and implemented policies aimed at absorbing external capabilities and fostering domestic technological innovation to strengthen their economies and enhance their economic and political capacities. The article concludes that, under two authoritarian regimes, and regardless of their paths to power and ideological particularities, both Park and Deng embraced technological innovation as a central strategy to achieve economic development and improve their international integration.